Protein Formulations Containing Polysorbates: Are Metal Chelators Needed at All? - Ema Valentina Brovč; Stane Pajk; Roman Šink; Janez Mravljak (MDPI AG, 2020)
Proteins are prone to post-translational modifications at specific sites, which can affect their physicochemical properties, and consequently also their safety and efficacy. Sources of post-translational modifications include oxygen and reactive oxygen species. Additionally, catalytic amounts of Fe(II) or Cu(I) can promote increased activities of reactive oxygen species, and thus catalyse the production of particularly reactive hydroxyl radicals. When oxidative post-translational modifications are detected in the biopharmaceutical industry, it is common practice to add chelators to the formulation. However, the resultant complexes with metals can be even more damaging. Indeed, this is supported here using an ascorbate redox system assay and peptide mapping. Ethylenediaminetetraacetic acid (EDTA) addition strongly accelerated the formation of hydroxyl radicals in an iron-ascorbate system, while diethylenetriaminepentaacetic acid (DTPA) addition did not. When Fe(III) was substituted with Cu(II), EDTA addition almost stopped hydroxyl radical production, whereas DTPA addition showed continued production, but at a reduced rate. Further, EDTA accelerated metal-catalysed oxidation of proteins, and thus did not protect them from Fe-mediated oxidative damage. As every formulation is unique, justification for EDTA or DTPA addition should be based on experimental data and not common practice.